Anticandidal activity of the extract and compounds isolated from Cyperus conglomertus Rottb - Ghaferah H. Al-Hazmi; Amani S. Awaad; Monerah R. Alothman; Saleh I. Alqasoumi (Elsevier, 2018)
The phytochemical screening of Cyperus conglomeratus showed that carbohydrates and/or glycosides, flavonoids, tannins, sterols and/or triterpenes, and proteins and/or amino acids are present. The fatty acid profile comprised major; palmitic, oleic, heptadecanoic, linoleic and minor; arachidonic, lignoceric, stearic, and myristic acid. Two compounds; namely, α-amyrin and β-sitosterol were isolated by the fractionation of unsaponifiable matter.The acute toxicity study showed that the reported after oral administration of the alcohol extract (TAE) showed that the plant was highly safe as the LD50 was more than 4000 mg/kg. These results were well supported by the sub-chronic toxicity, as the TAE administrated to rats for 15 consecutive days at dose 1000 mg/kg showed no alteration in the liver and kidney functions. Moreover, the extract of the plant exhibited anti-candidal activity against different Candida species. The most potent activity, (23.1 ± 2.1, 0.98 µg/ml) and (22.3 ± 0.53, 0.98 µg/ml), was obtained by the chloroform and total extract, respectively against Candida albicans. Keywords: Cyperus conglomeratus, Phytochemical screening, Antimicrobial activity, Fatty acids, α-amyrin, β-sitosterol